Capital Flow Waves to and from Switzerland before and after the Financial Crisis - Pınar Yeşin (Swiss Journal of Economics and Statistics, 2015)
This paper first shows that capital inflows to and outflows from financial centers were disproportionately affected by the global financial crisis. Switzerland was no exception. The paper then identifies waves of capital flows to and from Switzerland from 2000:Q1 to 2014:Q2 by using a simple statistical method. The analysis shows that private capital inflows to and outflows from Switzerland have become exceptionally muted and less volatile since the crisis. Further, strong and long-lasting `home bias' behavior can be observed for both Swiss and foreign investors. By contrast, net private capital flows have shown significantly higher volatility since the financial crisis, frequently registering extreme movements driven by extreme movements in bank lending flows. These findings suggest that the financial crisis generated a breaking point for capital flows to and from Switzerland.
Keywords: F21; F31; F32; 330; private capital flows; inflows; outflows; surges; stops; retrenchment; flight